2001
DOI: 10.1111/j.1754-4505.2001.tb00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Malocclusions and traumatic injuries in disabled schoolchildren and adolescents in Kuwait

Abstract: The present study was carried out to determine the prevalence of malocclusion and traumatic injuries in disabled children and adolescents attending the special-needs schools in Kuwait. Included in the study were 818 children (438 males and 380 females), in the age groups of 3-20 years, who have visual impairment, hearing impairment, physical handicaps, or developmental disorders. The mean age of participants was 11.9 years. The survey was carried out according to the methods of WHO. The prevalence of severe ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
76
4
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(90 citation statements)
references
References 16 publications
9
76
4
1
Order By: Relevance
“…In contrast to Muppa et al, [49], who reported the severity of anterior crowding and spacing to be higher among children with sensory disabilities, the current study revealed a higher prevalence of these types of malocclusions in children with neuropsychological disabilities and physical disabilities, again this may be contributed by poor development of oral-facial musculature with tongue and lips parafunctions common in cerebral palsy [45,46] as well as small dental arch size especially among Down's syndrome subjects [15].…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…In contrast to Muppa et al, [49], who reported the severity of anterior crowding and spacing to be higher among children with sensory disabilities, the current study revealed a higher prevalence of these types of malocclusions in children with neuropsychological disabilities and physical disabilities, again this may be contributed by poor development of oral-facial musculature with tongue and lips parafunctions common in cerebral palsy [45,46] as well as small dental arch size especially among Down's syndrome subjects [15].…”
Section: Discussioncontrasting
confidence: 53%
“…Down's syndrome has been reported to have high class III malocclusion [38,39], probably due to disharmony in cranial-base relationships [6,13,40], reduced dental arch size, decreased arch length, and inadequate maxillary size [15]. Meanwhile, cerebral palsy subjects who are often mentally retarded have high prevalence of class II [15,41] attributed to early eruption of primary teeth and abnormal tongue and head posture [15,[42][43][44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated a greater prevalence of tooth injuries among patients with cerebral palsy, mental handicaps and physical handicaps in comparison with healthy individuals, even when taking into account the fact that these individuals do not practice contact sports or radical physical activities. 8,11,[15][16][17] These findings serve as a warning to caregivers of individuals with mental disabilities and encourage a search for preventive measures, such as the use of mouth guards, the padding of objects and hard surfaces and the safe transport of these individuals in wheelchairs. 16 Regarding the risk factors associated to dental trauma, the most common are falls, collisions, automobile accidents, seizures, tooth grinding, dental caries, accentuated overjet and a lack of lip seal.…”
Section: Discussionmentioning
confidence: 99%